The impact of a typical student achievement teams use and integration of fragmented information in the collection of history students at the fifth grade literary (Journal of the College of Education for Women, 2019)
The goal of this research is to find the effects of both the studying students groupwhich has various educational levels and the integration of the fragmented information through or during the study of history subjects for the female students of the fifth secondary literary section.To achieve this study or case the researcher has chosen an experimental design or test by studying three groups: two are as mentioned above and the third is just ordinary team. In addition to that, there is a test after the experiment. The researcher chose on purpose female students of the literal section from two different secondary school Al Asil and Wahran both are secondary school for girls, and both are from directorate of education- Al Karkh 2nd district for the academic year 2014-2015 to make the experiment.The total number of students were 73 divided as follow: 24 students in the 1st experimental team, 25 students in the 2nd experimental team (integration of the fragmented information and 24 students in the 3rdteam which were taught in classical methods).The researcher was careful before starting her tests on the three groups of students, in choosing statistically equality in some of the variables, which she thinks may have negative effects on the experiment.The variables are final grade of history exam of the last year for every student, age of students calculated in months, parents educational level, and the test of prior knowledge of history.The researcher chose the educational material that should be taught which included the 1st and 2nd chapter from the modern history of Europe and America for the 5th literal secondary class or level. Then she put the behavioral goals depending on the general goals of the material and on the four levels (memory, understanding, practicing, and analysis) according to the Bloom’s taxonomy of learning Domains, which are 72 behavioral goals.The researcher also prepared teaching plans for the material that should be taught and for the final test which was a multiple choice test containing 50 questions. This final test has been presented to a group of experts and specialists in history, psychological science and teaching methods. The presentation to this group of experts was to examine, to verify the virtual honesty, to produce the difficulty factor or coefficient and to find the strength of its paragraphs. In addition to that, we should find its consistency and the same result of the test when the students repeat the same exam several times.The method called (partial way….)A correction has been made to the reliability factor by using the Spearman-Brown formula. The value of the factor was ( ) and it is accepted in educational and psychological studies.The researcher has personally completed her studies and tests on all the groups. It took a period of two months to do the experiment starting from 1/12/2014 and this was the first quarter of the academic school year 2014—2015.At the end of the experiment the researcher applied the final test for the history subject. She tested the first two groups on Wednesday 28/01/2015 and on Thursday 29/01/2015 for the classical third group.The researcher used the Scheffe’s method and the contrast unilateral analysis to process the data statistically. The results are the following:1-There are differences with statistical indications at the level (0.05) in the average of the students grades of the first group (which they are of various level of knowledge and grades) comparing to the average grades of the third and the classical group of students. The difference is in the benefit of the first group.2-There are differences with statistical indications at the level (0.05) in the average of the students grades of the second group (which they use the integration method of the fragmented information) comparing to the average grades of the third and the classical group of students. The difference is in the benefit of the second group.3-There are differences with statistical indications at the level (0.05) in the average of the students grades between the first group (which they are of various level of knowledge and grades) comparing to the average grades of the second group (which they use the integration method of the fragmented information). The difference is in the benefit of the first group.Below are the recommendations of researcher based on the results of her case study.1-To emphasis on the need to the attention of the ministry of education to use and teach the modern methods including the (method of various level of knowledge and grades in one group) and (the integration method of the fragments information).2-Offering and preparing developmental courses for the history teacher. The courses should include the modern methods including the (method of various level of knowledge and grades in one group) and (the integration method of the fragments information).3- Introducing in the books of history material the modern teaching plans and methods including the (method of various level of knowledge and grades in one group) and (the integration method of the fragments information).4- Applying the (method of various level of knowledge and grades in one group) and (the integration method of the fragmented information) when teaching other educational material.The researcher also suggests to practice and to apply similar experiments in:1- Other situations with different variables and groups other than the various level of education.2- In different stages and study phases other than the researcher has practiced and experimented.To conduct a study and make comparison between all-girls and all-boys schools insimilar case studies.